Ocular and Neuro-ophthalmic Manifestations Post COVID-19 Infection - Bista, Bipin; Yadav, Reena; Gupta, Sharad; Das, Sandip Sanyam; Rajak, Ashik; Acharya, Rajesh; Neupane, Rasik; Bista, Padam Raj (Journal of Nepal Health Research Council, 2023)
A 39-year-old male with a history of COVID-19 infection presented with ocular manifestations: dendritic ulcer in the left eye cornea followed by diplopia in the same eye. Extraocular motility was restricted in the levo-lateral gaze with maximum diplopia measuring 25? exotropia. Slit lamp biomicroscopy showed dendritic patterned lesion with diffused superficial punctate keratitis in the cornea. There are various reports associated with COVID-19 and the neuro-ophthalmic system. Although the clinicopathological aspect of COVID-19 and the neurological system is still to explicate. However, the patient showed gradual improvement with topical and systemic antiviral therapy and orthoptic exercise. This points to the need for detailed neurological and ophthalmic workup in symptomatic COVID-19 patients. Taking the risk of viral spread into serious consideration, a thorough evaluation is though mandatory. Keywords: COVID-19; dendritic ulcer; lateral rectus palsy; superficial punctate keratopathy